Implementation and impact of indigenous health curricula: a systematic review. Issue 9 (22nd June 2018) - Pitama, Suzanne G; Palmer, Suetonia C; Huria, Tania; Lacey, Cameron; Wilkinson, Tim
Abstract : Context: The effectiveness of cultural competency education in improving health practitioner proficiency and addressing health inequities for minoritised patient groups is uncertain. Identification of institutional factors that shape or constrain development of indigenous health curricula may provide insights into the impact of these factors on the broader cultural competency curricula. Methods: We undertook a systematic review using actor–network theory to inform our interpretive synthesis of studies that reported indigenous health curricula evaluated within medical, nursing and allied health education. We searched the MEDLINE, OVID Nursing, Educational Resources Information Center (ERIC), PsycINFO, EMBASE, Web of Science and PubMed databases to December 2017 using exploded MeSH terms 'indigenous' and 'medical education' and 'educational professional' and 'health professional education'. We included studies involving undergraduate or postgraduate medical, nursing or allied health students or practitioners. Studies were eligible if they documented indigenous health learning outcomes, pedagogical practices and student evaluations. Results: Twenty‐three studies were eligible for the review. In an interpretive synthesis informed by actor–network theory, three themes emerged from the data: indigenous health as an emerging curriculum (drivers of institutional change, increasing indigenous capacity and leadership, and addressing deficit discourse); institutional resource allocation to indigenous health curricula (placement within the core curriculum, time allocation, and resources constraining pedagogy), and impact of the curriculum on learners (acceptability of the curriculum, learner knowledge, and learner behaviour). Conclusions: Systemic barriers acting on and within educational networks have limited the developmental capacity of indigenous health curricula, supported and sustained hidden curricula, and led to insufficient institutional investment to support a comprehensive curriculum. Future research in health professional education should explore these political and network intermediaries acting on cultural competence curricula and how they can be overcome to achieve cultural competency learning outcomes. Abstract : The authors identify systemic barriers have limited the developmental capacity of indigenous health curriculum, supported and sustained hidden curricula and led to insufficient institutional investment to support a comprehensive curriculum.